Cellular response to synthetic drugs : a metabolomics approach - Chen, William Wei Ning. (2009)
Propranolol is a nonselective β-blocker of the β-adrenergic receptors, with the S-enantiomer being more active compared with the R-enantiomer. Clinically, it has been shown to be effective in hypermetabolic burn patients by decreasing cardiac work, protein catabolism and lipolysis. While gene expression profiles have recently been reported in children receiving propranolol treatment, variations from one individual to another may have influenced the data analysis. Using iTRAQ-coupled 2D LC-MS/MS analysis, we report here the first study of protein profile in vascular smooth muscle cells incubated separately with the two enantiomers of propranolol. Four types of cellular proteins including metabolic enzymes, signaling molecules, cytoskeletal proteins and those involved in DNA synthesis/protein translation displayed changes. The higher protein level of a number of enzymes involved in cellular anabolism and antioxidant activity in cells incubated with the S-enantiomer, as revealed by LC-MS/MS, was further supported by Real-Time PCR and Western blot analyses. Significantly, the increase in the anabolic activity associated with the higher level of metabolic enzymes was also supported by the higher intracellular concentration of the metabolic cofactor NAD+ which was a result of an increased oxidation of NADH. Our findings therefore provide molecular evidence on metabolic effect associated with propranolol treatment. The metabolic enzymes identified in our study may in turn be useful targets for future pharmaceutical interventions to reduce clinical side effects following propranolol treatment.